Building integrative environments for the improvement of scientific communication - Vrana, Radovan (Array, 2001)
This paper will present the review of the possibilities of collaboration on the Internet among scientists. As the Internet becomes more mature environment, it offers more sofisticated and complex support for communication and collaboration of different user groups thus creating virtual communities based on e-mail, Web, video, 3D virtual worlds applications. Despite the growing complexity of such resources, basic conceptual models behind those solutions are still relatively simple and offer enough space for improvement and optimization. Best IT supported collaboration solutions are usually provided by communities within disciplines themselves but some more general models can be shared among many disciplines. In this way new and more challenging collaborative digital environments for sharing vital scientific information are being created.